Anxiety-related symptomatology in young children on the autism spectrum. (February 2019) - Keen, Deb; Adams, Dawn; Simpson, Kate; den Houting, Jacquiline; Roberts, Jacqueline
Anxiety symptomatology is frequently reported in autistic children, and the prevalence of anxiety disorder is estimated at around 40%. However, most studies have focused upon children of age 8 years or above, so little is known about early signs of anxiety in younger children with autism. This study sought to describe anxiety-related symptomatology in 95 5- to 6-year-old autistic children using the Anxiety Scale for Children with Autism Spectrum Disorder. Wide variability was found in levels of symptomatology with the most frequently reported items within the 'uncertainty' subscale and the least frequently reported items in the 'anxious arousal' subscale. Comparisons of those with scores less than or greater than 70 on adaptive behaviour suggests some influence of ability on presentation of anxiety-related symptomatology.